Ambient pressure effect on non-premixed turbulent combustion of CH4–H2 mixture. (20th July 2016) - Ziani, L.; Chaker, A.
Abstract: The present work is devoted to the study of the effect of ambient pressure on non-premixed turbulent combustion of a mixture of 20% of hydrogen and 80% of methane. The simulations were conducted using the PDF approach and modified k - ε turbulence model. The flamelet model was used with the GRI 2.11 detailed kinetic mechanism. The flame consists of two coaxial jets of air and a jet of CH4–H2 mixture with pilot flame. After validating the model used we have varied the ambient pressure from 1 to 10 atm. We observed that the increase of ambient pressure leads to a slight increase of the flame temperature and the mass fraction of NO and a decrease in the radial and axial expansions. Highlights: Simulation of turbulent diffusion flame with the PDF approach using the flamelet model and the modified k-epsilon model. Evaluation of the combustion model within non-premixed turbulent combustion with coaxial geometry at high pressure. Evaluation of the effect of ambient pressure on methane enriched with hydrogen flame. Increase ambient pressure shrinks the flame.